KEJADIAN LUAR BIASA CHIKUNGUNYA DI KABUPATEN LOMBOK BARAT-NUSA TENGGARA BARAT DITINJAU DARI FAKTOR LINGKUNGAN RUMAH DAN PERILAKU - Diana Andriyani Pratamawati (Balai Penelitian dan Pengembangan Kesehatan Baturaja, 2017)
Abstract Provincial Health Office of West Nusa Tenggara (NTB) in 2010 have reported an increase in cases of Chikungunya in West Lombok regency as many as 223 patients. In 2011 (January-April) is still found Chikungunya patients in West Lombok district sporadically. The aim of research to provide an environment that is allegedly associated with the onset of outbreaks of chikungunya, and to know the level of knowledge, attitudes, and practice of local communities related to prevention chikungunya.Design analytic epidemiologic research with case-control study design, namely the survey time point in the study sample. Research Location in Lombok Barat West Nusa Tenggara (NTB) was conducted in April-May 2011. The total number of 132 samples consisting of a sample of 66 cases and controls 66. The results showed that chikungunya outbreaks in two villages in West Lombok regency have five factors play an important role among other factors productive age (15-49), factor in the type of work, a factor of mosquito breeders place, a factor of cloth hanging (curtain), and the factor of knowledge, attitude, practice (KAP) community about the chikungunya disease yet quite well. Need to increase the knowledge, attitudes, and practise of the community in the prevention of chikungunya through counseling / health promotion media intensive chikungunya prone season so expect the behavior patterns of society are not the cause of the recurrence of outbreaks of chikungunya in the future.